Fostering the Entrepreneurial Spirit of Students through Digital Marketing in the Sharia Banking Study Program at STAIN Teungku Dirundeng Meulaboh - Muliza; Qadrunnada, Annisa; Rinaldi , Mikhral; Hijrah; Andhika , M. Rezki (Universitas Nahdlatul Ulama Surabaya, 2025)
In the long term, the Indonesian government has set a target to achieve an entrepreneurship ratio of 8% by 2045. This is certainly not an easy feat and requires the right approach to produce resilient entrepreneurs who are ready to compete in the digital and global era. Digitalization is not only about entering digital markets but also involves using smart factories and the Internet of Things (IoT). This community service activity was carried out with the aim of fostering the spirit and ability of digital marketing-based entrepreneurship among students of the Sharia Banking Study Program at STAIN Teungku Dirundeng Meulaboh. The activity was motivated by the low level of student awareness regarding entrepreneurial opportunities in the digital era, even though access to and the potential of digital technology are widely available. Through a participatory training approach, students were provided with fundamental knowledge about entrepreneurship, digital marketing strategies, the use of social media as a promotional tool, and an introduction to marketplaces as business platforms. The implementation methods include interactive lectures, case studies, and hands-on practice in creating content and digital marketing strategies. The results of the activity showed an increase in students' understanding and interest in digital entrepreneurship, as well as the emergence of initiatives to start online-based businesses individually or in groups. This activity is expected to serve as a starting point in shaping the entrepreneurial spirit of students who are adaptive to the development of the digital economy.